Adverse prognostic influence of diabetes mellitus and hyperglycemia on the clinical course of brain infarct: a review of its causes with special reference to the pathogenesis of hyperglycemia in the acute phase of stroke - Charles André; Sérgio Augusto Pereira Novis (Arquivos de Neuro-Psiquiatria)
In non-diabetic patients, the appearance of hyperglycemia in the acute phase of stroke is related to the extension of cellular injury, and hence to the physiologic stress response. In animal models of ischemic insult, the deleterious effects of hyperglycemia depend heavily on the production of lactic acid «via» activation of the glycolitic anaerobic pathway. The abnormal production of lactic acid and consequent tissular acidosis appear mainly in the early post-reperfusion period, or in states of marked but partial reduction of blood flow. A direct reduction of cerebral blood flow and, perhaps, the production of a hyperosmolar state may contribute to worsening of the ischemic injury. In diabetic patients, previous hemoreologic and microcirculatory changes, and a greater susceptibility to infections may additionally reduce the chances of complete recovery after stroke.